Pengaruh Citra Merek dan Harga terhadap Loyalitas Pelanggan Indomie Goreng dengan Kepuasan sebagai Variabel Intervening - Richardus Mosa Leke; Henny Welsa; Agus Dwi Cahya (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to examine and determine: the effect of brand image and price on customer loyalty of indomie goreng with satisfaction as an intervening variable. The method used in this study is a quantitative method with primary data obtained through a questionnaire (questionnaire). The sample of this study was 100 respondents with purposive random sampling technique which was then processed using the spss 21.0 data processing application and analyzed using multiple linear analysis. The results of the study indicate that brand image has a positive and significant effect on customer loyalty. Price has a positive effect on customer loyalty. Brand image and price simultaneously have a positive effect on customer loyalty. Brand image has a positive and significant effect on customer loyalty with satisfaction as an intervening variable. Price has a positive and significant effect on customer loyalty with satisfaction as an intervening variable.